2020
DOI: 10.3390/su12125078
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Sustainable Energy Policies for the Promotion of Renewable Energy Sources

Abstract: Meeting the rising energy demand and limiting its environmental impact are the two intertwined issues faced in the 21st century. Governments in different countries have been engaged in developing regulations and related policies to encourage environment friendly renewable energy generation along with conservation strategies and technological innovations. It is important to develop sustainable energy policies and provide relevant and suitable policy recommendations for end-users. This study presents a review on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
140
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 296 publications
(144 citation statements)
references
References 86 publications
1
140
0
3
Order By: Relevance
“…An additional analysis of subsidies for energy efficiency improvement measures has shown that the elimination of artificial price reductions alone is not enough to achieve long-term energy efficiency goals [35]. In many countries, subsidies for innovative energy performance measures, in particular those using renewable energy, are used to increase the energy efficiency of a building [36]. Other researchers suggest that most appropriate measures are demonstration projects and soft loans for energy efficiency measures [37].…”
Section: Resultsmentioning
confidence: 99%
“…An additional analysis of subsidies for energy efficiency improvement measures has shown that the elimination of artificial price reductions alone is not enough to achieve long-term energy efficiency goals [35]. In many countries, subsidies for innovative energy performance measures, in particular those using renewable energy, are used to increase the energy efficiency of a building [36]. Other researchers suggest that most appropriate measures are demonstration projects and soft loans for energy efficiency measures [37].…”
Section: Resultsmentioning
confidence: 99%
“…However, the proposed technique yield stable ROMs and also carry error bounds formula with low frequency-response approximation error. Figs ( 4, 5) of example 1 and Figs (8,9,10,11) of example 2 respectively provide a comparison of ROMs obtained by using existing ( [49], [51], [52], [53]) and the proposed approach with the original system for the frequency response Bode plot (magnitude, [54] and Proposed Technique WZ's Technique [54] Proposed Technique…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…In this section, numerical examples of the DFIG based variable-speed wind turbine (double-cage induction generator) for the power system (induction model, current model) based on the multi-input multi-output discrete-time are given to show the comparison of the proposed technique with the existing frequency-limited model reduction technique for the LTI continuous-time system. Figs (4,5,6,7,8,9,10,11,12,13) represent the Bode plot (magnitde, phase) comparison of corresponding ROMs obtained by existing ( [51], [52], [53], [54], [55], [56]) and the proposed approache with the original system, each Fig contains subfigures which represent output/input Bode plot (magnitude, phase). Table . 5 and 6 provide frequency response error comparison existing ( [51], [52], [53], [54], [55], [56]) and the proposed approaches.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…Some countries that have mastered nuclear power generation technology (such as France, the United States, China, etc.) view the active promotion of nuclear energy construction as an important energy construction policy [ 2 ]. In total, 31 countries operate 417 nuclear reactors and the total operating capacity has reached 370 GW, which is a new historic maximum [ 3 ].…”
Section: Introductionmentioning
confidence: 99%